Molecular detection of Coxiella burnetii in livestock farmers and cattle from Magdalena Medio in Antioquia, Colombia (2020)
ABSTRACT : Coxiella burnetii causes Q fever in humans and coxiellosis in animals. In humans, it causes acute febrile illnesses like influenza, pneumonia, hepatitis, and chronic illnesses such as endocarditis, vascular infection, and post-infectious fatigue syndrome. It is widely distributed worldwide, and its main reservoirs are sheep, goats, and cattle. This study aimed to determine the frequency of C. burnetii infection using molecular detection and to identify the associated factors in livestock farmers and cattle from the Magdalena Medio region of Antioquia, Colombia. Using real-time polymerase chain reaction (PCR), molecular detection was performed for the IS1111 insertion sequence of C. burnetii using genomic DNA collected from the peripheral blood of 143 livestock farmers and 192 cattle from 24 farms located in Puerto Berrío, Puerto Nare, and Puerto Triunfo. To confirm the results, bidirectional amplicon sequencing of 16S rRNA was performed in four of the positive samples. Additionally, factors associated with C. burnetii were identified using a Poisson regression with cluster effect adjustment. Real-time PCR showed positive results in 25.9% and 19.5% of livestock farmer samples and cattle samples, respectively. For livestock farmers, factors associated with C. burnetii were the area where the farm was located [Puerto Berrío, adjusted prevalence ratio (aPR): 2.13, 95% confidence interval (CI): 1.10-4.11], presence of hens (aPR: 1.47, 95% CI: 1.21-1.79), horses (aPR: 1.61, 95% CI: 1.54-1.67), and ticks (aPR: 2.36, 95% CI: 1.03-5.42) in the residence, and consumption of raw milk (aPR: 1.47, 95% CI: 1.26-1.72). For cattle, the factors associated with Coxiella genus were municipality (Puerto Nare; aPR: 0.39, 95% CI: 0.37-0.41) and time of residence on the farm (≥49 months; aPR: 2.28, 95% CI: 1.03-5.20). By analyzing sequences of the 16S rRNA molecular marker, C. burnetii infection was confirmed in livestock farmers. However, in cattle, only the presence of Coxiella-type bacteria was identified. Further research is necessary to determine the potential role that these types of bacteria have as etiological agents for disease in livestock farmers and cattle from the study area.